AQIQAH SETELAH DEWASA (Studi Sanad dan Matan Hadis) - Nispan Rahmi (Syariah: Jurnal Hukum dan Pemikiran, 2013)
Al-Baihaky and al-Bazzar has narrated the hadith about "'Aqiqah after Adult." This hadith is not only famous among the scholars of hadith, but also on the part of Muslim society to exist among those who practice it, there are allow and do aqiqqah after adults, but some are rejected because they do not correspond to the meaning aqiqah itself. Aqiqah is the hair that grows on the head of the baby when born. Aqiqah also means the name of the slaughter of animals slaughtered for the newborn child. in terms the quality sanad of hadith is dlaif (weak). Then, why some jurists use these traditions to legitimize the permissibility of carrying out aqiqah as an adult? Or maybe the hadith hasan or even authentic quality. This question inspires the author to examine the hadith, whether authentic or dlaif? The findings of this study indicate that the quality is very dlaif and matan (the text of the report) contained irregularities..